Surface-Modified Nanofibrous PVDF Membranes for Liquid Separation Technology - Boyraz, Evren; Yalcinkaya, Fatma; Hruza, Jakub; Maryska, Jiri (Materials (Basel, Switzerland), 2019)
Preparing easily scaled up, cost-effective, and recyclable membranes for separation technology is challenging. In the present study, a unique and new type of modified polyvinylidene fluoride (PVDF) nanofibrous membrane was prepared for the separation of oil-water emulsions. Surface modification was done in two steps. In the first step, dehydrofluorination of PVDF membranes was done using an alkaline solution. After the first step, oil removal and permeability of the membranes were dramatically improved. In the second step, TiO2 nanoparticles were grafted onto the surface of the membranes. After adding TiO2 nanoparticles, membranes exhibited outstanding anti-fouling and self-cleaning performance. The as-prepared membranes can be of great use in new green separation technology and have great potential to deal with the separation of oil-water emulsions in the near future.
Keywords: PVDF; electrospinning; membrane; filtration; surface modification; nanofiber